A Canny operator road edge detection method based on color features. (September 2020) - Wang, Shigang; Wu, Shukun; Wang, Xuesong; Li, Zhenglin
Abstract: The road edge detection method, proposed by us, highlights the morphological and color features of the road in the image. The method performs color space conversion and color feature screening on color images containing road information, and Canny operator is used for edge detection. Then the edge detection results are detected by straight lines, and the road edges are detected and marked based on the principle of Hough transform. The experiment of edge detection on road pictures with complex background proves that the detection method can better detect the road edge. The novelty of this method is to combine several principles such as color feature screening, Canny operator and Hough transform. Therefore, a new method of road edge detection is formed.